PENGARUH UKURAN PERUSAHAAN (FIRM SIZE), PROFITABILITAS,LIKUIDITAS, PRODUKTIVITAS, DAN LEVERAGE TERHADAPPERINGKAT OBLIGASI - INDAH SURYA, ERNY (Jurnal Akuntansi AKUNESA, 2015)
This research aims to investigate the influence of firm size, profitability,liquidity, productivity, and leverage to bond ratings. Financial performanceconsists of firm size (total assets), profitability (return on assets), liquidity(current ratio), productivity (total assets turnover), and leverage (debt ratio). Thesamples in this research were obtained by using purposive sampling methodwhich consists of bonds issued by non-financial companies listed on theIndonesian Stock Exchange for the period 2013-2014 and rated by Pefindo. Thisresearch uses a model of multiple linear regression analysis. The finding of thisresearch that firm size, productivity, and leverage variables have influence tobond ratings. while profitability and liquidity are variables which have no effectto bond rating. Keywords: bond ratings, firm size, profitability, liquidity, productivity, leverage